Training future teachers communicative activities in the educational process of high school (Pedagogy of Higher and Secondary Education, 2013)
Maksymenko I. G., Pinskaya O. L. Training future teachers communicative activities in the educational process of high school.The essence of communicative activity, organization technique of communicative directed education as a condition of effective students’ training to the communicative activity are disclosed in the article.
Keywords: communication; activity; communicative activity; communicative directed education